Evaluation on Students' Service Design Concepts using the Principles of Service Innovation and Design Process - Majid, Ahmad Zuhairi Abdul (Mattingley Publishing Co., Inc., 2020)
his paper is a review on service innovation and design education in Malaysia specifically for Product Design programme at School of The Arts, Universiti Sains Malaysia. With new design thinking, principles and methods for services design and development will change the value of designers in education and creative industries that are suitable for the next generation. Since 2012, we have started to adapt some of the basic methods and exploring new ideas in developing new services or servicescapes for health services and point of sales enhancement. This paper shows some of the successful design developed by the students. All selected design developments were chosen from their design reports which have been assessed over the last several years since 2014. A compilation of research and development of each selected work shall bepresented and also can be compared through design positioning and matrixes. Therefore, this review can be seen as significance to the service industries that shall give more opportunities for young designers to contribute. The real benefit from service innovation education is to encourage sustainability in human lifestyle. To achieve something that is less stressful, good communication between human, responsible design and satisfaction in every aspect of life that relate to services, especially the people-processing type of service. Ultimately, the professional practice of service innovation will be recognized in Malaysia.Keywords:design thinking, service design, servicescape, innovation1. INTRODUCTIONThe review is to show how students can achieve their understanding and design thinking towards issues on service innovation design. Designers' contribution to the services industry is crucial to promoting the country's economic growthalthough product development is still needed for the nation. In Malaysia, Service sector plays an important part alongside the manufacturing sector in the country’s development growth. Findings from various countries show that more than 60 percent gross income are coming from service sectors [1]. For example, the ratio of intangible investment to GDP has risen in Japan and in most other developed countries like USA, UK, Germany, France and Italy [2]. The service sector has played an important role in the growth and development process of the Malaysian economy. Within one short generation, a dramatic shift happened in how we buy things, interact with companies, do our jobs and communicate with each other just because of the pervasive digital technology [3]. It is the best example of technology that can change people or users in their everyday life. Furthermore, with the rapid advancement of technology and renowned as the industry revolution 4.0 then of course a range of